2015
DOI: 10.3354/esr00654
|View full text |Cite
|
Sign up to set email alerts
|

Trialling exudate-based enrichment efforts to improve the welfare of rescued slow lorises Nycticebus spp.

Abstract: Slow lorises Nycticebus spp. are heavily targeted in the illegal animal trade throughout Southeast Asia. Because lorises are venomous, many have their teeth inhumanely removed by animal traders in order to 'tame' them to live as pets or to be used for tourist photography. Confiscated animals are brought to rescue centres where captive care and rehabilitation has proven challenging. Many rescue centres report high mortality, high rates of abnormal behaviour, and low rates of successful reintroductions. Most cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…While data are lacking, given the age of the primates involved, their physical condition as observed in the markets, and the conditions in which they were packed, it is inevitable that these transports lead to high levels of mortality. The treatment of slow lorises, and to a lesser extent, gibbons and siamangs are particularly cruel, given that they routinely have their canines (gibbons) or their canine‐shaped first premolars, canines and incisors (the latter forming the toothcomb in slow lorises) either pulled out or cut off [Gray et al, ]. Apart from the immediate physical pain this procedure causes the animals, it often leads to infections, secondary abscesses and, for slow lorises, is a major cause of death [Madani & Nekaris, ; Moore et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…While data are lacking, given the age of the primates involved, their physical condition as observed in the markets, and the conditions in which they were packed, it is inevitable that these transports lead to high levels of mortality. The treatment of slow lorises, and to a lesser extent, gibbons and siamangs are particularly cruel, given that they routinely have their canines (gibbons) or their canine‐shaped first premolars, canines and incisors (the latter forming the toothcomb in slow lorises) either pulled out or cut off [Gray et al, ]. Apart from the immediate physical pain this procedure causes the animals, it often leads to infections, secondary abscesses and, for slow lorises, is a major cause of death [Madani & Nekaris, ; Moore et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many contact points between the broken cambium of the tree during gouging and/or the tree's gum during intake that may act as a source of friction and remove any plaque. Gum provided to captive lorises is either spread on branches or placed into drill holes of thick branches [Gray et al, ]. It is uncommon for a captive slow loris to gouge offered branches.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the large disparity between foraging times in the wild and in captivity, we believe this to be inadequate and would recommend two or more feeds per day. The provision of gum also significantly extended feeding time [Fitch‐Snyder and Schulze, ; Cabana and Plowman, ; Gray et al, ]. Bowls or plates were reported to be used in over 92.3% of collections.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Cabana & Plowman (2014, this Theme Section) show that by feeding pygmy lorises reared at a UK zoo a diet based on field evidence, abnormal behaviour decreased and desirable behaviours such as travelling and feeding increased, and that the study subjects found the naturalised diet far more palatable. Similarly Gray et al (2015, this Theme Section) also examined exudate consumption in wild-caught slow lorises (N. javanicus, N. coucang, N. menagensis) confiscated from the pet trade. Because of a destructive and cruel practice, whereby traders clip out the gouging teeth of slow lorises to prevent them from biting, many confiscated animals no longer have the faculty to gouge.…”
Section: Current Knowledge and Contribution Of The Theme Sectionmentioning
confidence: 99%
“…Because of a destructive and cruel practice, whereby traders clip out the gouging teeth of slow lorises to prevent them from biting, many confiscated animals no longer have the faculty to gouge. Gray et al (2015) thus trialled a series of gum-based enrichments also designed to suit animals that no longer had teeth. They found that the enrichment devices prolonged feeding and foraging times, and also gave the animals more opportunities to spend time off the floor, where they were more likely to exhibit stereotypic behaviours.…”
Section: Current Knowledge and Contribution Of The Theme Sectionmentioning
confidence: 99%